Association of Hirschsprung disease with Waardenburg syndrome and role of gene studies: A review of 2 cases - Dipak, Niraj Kumar; Parab, Siddharth; Nage, Amol; Kumar, Abnish (Indian Journal of Child Health, 2018)
Background: Waardenburg-Shah syndrome type 4 is an association of Waardenburg syndrome with Hirsch sprung disease. Three disease-causing genes have been identified so far: Endothelin receptor type B encoding the endothelia-B receptor, EDN3 encoding an endothelia receptor ligand and Sry-like HMG bOX10 (SOX10) encoding the SOX10 transcription factor. Case Report: This is a review of 2 cases with variable onset of presentation and extent of aganglionic segment. Intervention/Outcome: In case 1, primary pull-through, as definitive surgical correction was done as a single procedure, whereas in case 2, required ileostomy with a plan of definitive surgery later on. Message: Mutation studies are helpful in characterization of the syndrome and counseling to the family. Furthermore, prognosis depends on the length of the ganglionic segment.